Predicting work engagement of employees at Dundee Precious Metals Mine in Tsumeb, Namibia - Pieters, W.R.; Von Spiegel, A. (Namibian Journal for Research, Science and Technology, 2024)
The profit margins of organisations are noticeably influenced by their competitive advantage inclusive of engaged employees. The aim of this study was to investigate the impact of job demands-resources on job satisfaction and work engagement of employees at Dundee Precious Metals Mine in Tsumeb. Job resources play a critical role in the job attitudes employees experience/develop (job satisfaction). Job satisfaction is regarded as the key motivating factor that enhances work engagement of employees. A quantitative, cross-sectional research design was employed, and data was collected through a questionnaire. A sample of n=150 participants was selected using random sampling. This study found a positive relationship between job resources (growth opportunities and advancement opportunities), job satisfaction and work engagement. Growth opportunities and advancement opportunities predicted job satisfaction. Job resources (growth and advancement opportunities) and job satisfaction predicted work engagement of employees. This study recommends interventions such as job rotation and internal training to enhance growth opportunities. It is also recommended to involve employees in the decision-making process, establish/implement recognition and rewards policies, educate staff on financial planning and ensure that fair payment and benefits are provided throughout the organisation. The organisation may also consider investing in interpersonal training and conflict resolution skills. The study adds to the knowledge within Industrial Psychology and the Namibian work setting.